2019
DOI: 10.3390/ijms21010068
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Effects of BTKi on T Cells for Effective Immunotherapy against CLL

Abstract: B-cell receptor (BCR) signaling and tumor–microenvironment crosstalk both drive chronic lymphocytic leukemia (CLL) pathogenesis. Within the microenvironment, tumor cells shape the T-cell compartment, which in turn supports tumor growth and survival. Targeting BCR signaling using Bruton tyrosine kinase inhibitors (BTKi) has become a highly successful treatment modality for CLL. Ibrutinib, the first-in-class BTKi, also inhibits Tec family kinases such as interleukin-2–inducible kinase (ITK), a proximal member of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 92 publications
(133 reference statements)
1
40
0
Order By: Relevance
“… 79 In addition, ibrutinib polarizes the T-cell population toward effector cells and reduces their exhaustion marker expression, which possibly enables the adaptive immune system to a more capable immune response. 56 , 80 B-cell activation and a subsequent increase in IgG levels, which are both inhibited by ibrutinib, are specifically increased in patients with severe COVID-19. 45 , 68 , 76 Because of these immunomodulatory effects, ibrutinib, and perhaps the more selective BTK inhibitors as well, might be beneficial in the early and late stages of COVID-19.…”
Section: Immunomodulation In Relation To Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“… 79 In addition, ibrutinib polarizes the T-cell population toward effector cells and reduces their exhaustion marker expression, which possibly enables the adaptive immune system to a more capable immune response. 56 , 80 B-cell activation and a subsequent increase in IgG levels, which are both inhibited by ibrutinib, are specifically increased in patients with severe COVID-19. 45 , 68 , 76 Because of these immunomodulatory effects, ibrutinib, and perhaps the more selective BTK inhibitors as well, might be beneficial in the early and late stages of COVID-19.…”
Section: Immunomodulation In Relation To Sars-cov-2mentioning
confidence: 99%
“… 54 Ibrutinib, as well as the more selective BTK inhibitors, reduces the (over)activated T-cell state of CLL patients, as measured by lower plasma cytokine levels and decreased exhaustion. 47 , 55 , 56 These observations are probably the indirect result of on-target (BTK) effects on leukemia cells, resulting in decreased suppressive interactions of the malignant B cells with T cells. 57 Sorafenib and sunitinib treatment also results in lower PD-1 expression on CD4 + and CD8 + T cells in vivo and in vitro, respectively.…”
Section: Impact Of the Main Tkis On The Immune Responsementioning
confidence: 99%
“…In chronic lymphocytic leukemia (CLL), it has been demonstrated that ibrutinib profoundly reshapes the T cell compartment, improving T cell function. Ibrutinib induces expansion of memory T cells, Th1 polarization, reduces the expression of inhibitory receptors (i.e., PD-1 and CTL-4), and improves immune synapse between T cells and CLL cells [ 103 , 104 ]. However, no data are available for FL in this regard.…”
Section: T Cells: Fundamental Actors In Fl Pathogenesis Modulated mentioning
confidence: 99%
“…Indeed, and at variance from chemoimmunotherapy, ibrutinib mitigates the immune dysregulation induced by CLL, by modifying the absolute number of T-cells (25)(26)(27)(28), the T-cell receptor repertoire (26,29), the T-cell maturation (27,28), the Th1 and Th2 polarization (24)(25)(26)(27), the Th17 and Treg cell balance (25,27,28), the T cell inhibitory receptors and function (25,(27)(28)(29). These effects, all modulated toward an anti-tumor T-cell response, have been nicely reviewed (30)(31)(32). Regarding the Th1 and Th2 polarization, it has been shown that ibrutinib may contribute to revert the Th2-dominant response observed in CLL, thus influencing T-cell mediated cancer immune surveillance, in vitro and in a mouse model (24) and in patients treated with ibrutinib (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%